Ascites complications risk factors of decompensated cirrhosis patients: logistic regression and prediction model - Xiaolong Zheng; Wei Wei (BMC Gastroenterology)
Abstract Objective The study mainly aim at exploring the ascites risk factors among decompensated cirrhosis patients via constructing the prediction model of ascites incidence. Methods Here, we recruited 148 decompensated cirrhosis patients for analysis, their laboratory tests and complications recorded. T-test, chi-square test, single-factor logistic regression, multi-factor logistic regression, and nomogram model were used to investigate the ascites occurred factors in decompensated cirrhosis patients with ascites. To validate the data analysis results, we applied the receiver operating characteristic (ROC) curve, calibration curve, and decision curve analysis (DCA) to evaluate the discrimination, calibration, and clinical usefulness of the prediction model, respectively. Results Serum creatinine levels were higher in the cirrhotic ascites group than in the non-ascites group. The ascites group had lower albumin and serum sodium levels, as well as a lower incidence of variceal bleeding and varicose veins compared to the non-ascites group. Conclusion Varicose veins, variceal bleeding, and serum sodium levels are significant factors contributing to ascites development in cirrhosis. Furthermore, decreased serum albumin and elevated creatinine levels are important indicators of poor prognosis. Nomograms can improve clinicians’ informed decision-making for patients with decompensated cirrhosis, ultimately reducing ascites risk.